Streaming media and cultural memory in a postdigital society - Gambarato, Renira Rampazzo, author. Link
1 online resource (vi, 146 pages).
Keywords: "This book offers a relevant contribution to the studies of streaming media and transmediality with an original approach of cultural sustainability perfectly intertwined with cultural memory beyond borders. By critically reflecting on popular streaming media series, the book identifies their impact on the global circulation of cultural memory, their learning potential for educational purposes, and the societal challenges and opportunities that emerge from the ubiquitous streaming media penetration and potential for participatory practices. It also investigates how series available worldwide on commercial platforms such as Netflix and HBO Max contribute to the global circulation of cultural memories, in addition to illuminating the ethical, (un)sustainable and educational concerns involved in the fictionalization of the past. Drawing on the authors' expertise in media studies and history, this transdisciplinary book will interest scholars in the fields of media studies, cultural studies, memory studies, history, transmedia studies, education, post-digital studies, television studies, social communication, sociology and philosophy"--